MENJADI INDONESIA: IKONISITAS SUNDA-INDONESIA DALAM PUISI ‘TANAH SUNDA’ DAN ‘TANAH AIR’ KARYA AJIP ROSIDI (Become Indonesia: Sunda-Indonesia Iconicity in The Poetry of ‘Tanah Sunda’ and ‘Tanah - Teddi Muhtadin (Balai Bahasa Sulawesi Selatan, 2023)
After the Japanese occupation, regional languages and Dutch were prohibited from being used. Only Japanese language and Indonesian language are permitted to be used. Because of this, Sundanese language and literature declined, while Indonesian language and literature were pushed forward. Entering the independence era, the situation in Sundanese literature was getting worse, because from 1945 to 1950 the Indonesian people were constantly waging war against Japan, the Allies and the Netherlands. This research will focus on the Sundanese movement that occurred in the 1950s, especially those represented through the poem Tanah Sunda and Tanah Air by Ajip Rosidi. The purpose of writing this article is to see (1) the Sundanese movement emerged simultaneously with the emergence of the form of poetry in Sundanese literary treasures, and (2) the Sundanese movement and the